Dwarf shrub vegetation of rock ledges and clefts in the Pamir Alai Mountains (Middle Asia: Tajikistan) - Nowak, Arkadiusz; Nowak, Sylwia; Nobis, Marcin; Nobis, Agnieszka (Acta Botanica Croatica, 2016)
The paper presents the results of phytosociological researches on rocky slope vegetation in Tajikistan with the aim to establish a comprehensive syntaxonomical classification system. Field studies were conducted in 2010–2014 in Pamir Alai ranges and Pamirian plateau. Nearly 500 relevés documenting rock and scree vegetation were made according to the Braun-Blanquet method. Numerical analyses of selected 58 relevés representing dwarf shrub vegetation on rock ledges made it possible to distinguish: Ephedro glaucae- Spiraeion baldschuanicae and Ephedrion regeliano-fedtschenkoi alliances, as well as Spiraeetum baldschuanicae, Rhamnetum coriaceae, Pentaphylloidetum parvifoliae and Pentaphylloidetum dryadanthoidis associations, community of Ephedra glauca and community of Rhamnus minuta. The classification of vegetation of dwarf shrubs on rock walls occurring in the Pamir Alai Mts is proposed. Because of the species composition, physiognomy and microhabitat conditions, the plant communities were included into Artemisio santolinifoliae- Berberidetea sibiricae class Ermakov et al. 2006. The main factors determining the species composition of the classified associations seem to be the elevation above sea level.The newly described syntaxa are largely defined by species restricted to very narrow ranges in Middle Asia